Möbius Syndrome: characterization of children treated in an institution in Fortaleza-CE - 10.5020/18061230.2012.p37 - Brasileiro, Ismênia de Carvalho (2012)
Objective: To describe the socio-demographic and clinical characteristics of a group of children with Möbius syndrome. Methods: The quantitative, descriptive, documentary and transversal research, was performed at an early intervention medical institution in the city of Fortaleza-CE, Brazil in 2009. Results: The analysis of nine children in attendance revealed that their mothers were pregnant at the early average age of 24, with stable relationships, half of them graduated from high school and the other half, from fundamental school. Most families (77.8%) had a monthly income below the minimum wage. All children were born at term, the majority by cesarean section (77.8%). Neonatal intercurrences were verified in 77.8% of children, which justified their early introduction to the counseling center for child development. Regarding the peculiar characteristics of the syndrome, facial palsy, clubfeet and hypotonia were present in all cases, and strabismus in 88.9% of them. An amount of 55.6% of children showed other abnormalities, such as lack of fingers and toes. Cytotec® had been used as a measure to terminate pregnancy in 55.6% of cases. Conclusion: Children with Möbius are mostly born from mothers which underwent full term pregnancies, living up with monthly minimum wage, in stable relationships. Although being born at term, the children went through neonatal complications. Bilateral facial palsy, strabismus, club feet, and hypotonia were the most related clinical characteristics.